PUBLICATIONS OF THE WEEK. (Bookseller, 2003)
The article presents a list of books on various topics such as agriculture, architecture and town planning, botany, biology and others published as of January 2003. Some of the books are "Stars in My Eyes: A Life in Show Business," by Max Bygraves, "Saint Therese of Lisieeux: A Short Life," by Kathryn Harrison, "Broadcasting Freedom: The Cold War Triumph of Radio Free Europe and Radio Liberty," by Arch Puddington.